Measuring young U.S. children's parasocial relationships: toward the creation of a child self-report survey. Issue 2 (3rd April 2017) - Richards, Melissa N.; Calvert, Sandra L.
Abstract: Adults and children form one-sided, emotionally tinged relationships with media characters known as parasocial relationships. Studies have measured adult conceptions of their own parasocial relationships and parent perceptions of their children's parasocial relationships, but little is known about how to quantify young children's perceptions of their own parasocial relationships. In this study, a child self-report survey was developed based on prior parental surveys and behavioral measures to operationalize children's parasocial relationships. Results revealed that 2–6 year-old U.S. children can name and report about their favorite media characters, who were the target for assessing parasocial relationships. Factor analyses indicated three components of children's parasocial relationships: attachment and friendship, humanlike needs, and social realism . Although the internal consistency improved with age on attachment and friendship and social realism, only the attachment and friendship subscale reached conventional acceptable levels of internal consistency. This study provides a new method for operationalizing children's parasocial relationships through child interview and describes future research directions for improving the internal consistency of the child subscales.